(untitled) (Journal of Pharma Insights and Research, 2025)
α, β-Unsaturated aryl ketones constitute a fundamental class of organic compounds featuring a conjugated enone system linked to an aromatic moiety. The characteristic structural framework comprises a carbon-carbon double bond positioned adjacent to a carbonyl group, with an aryl substituent attached to the carbonyl carbon. This unique electronic arrangement results in enhanced chemical reactivity and biological activity profiles. These compounds serve as versatile intermediates in organic transformations, particularly in Michael additions, aldol condensations, and cycloaddition reactions. The electrophilic nature of the β-carbon facilitates nucleophilic attack, making these molecules valuable synthetic building blocks. Extensive pharmacological investigations have revealed significant antimicrobial, anticancer, anti-inflammatory, and antioxidant properties. Chalcones, representing the most prominent subclass, demonstrate particular promise in drug discovery programs. Various synthetic approaches including Claisen-Schmidt condensation, Wittig reactions, and palladium-catalyzed cross-coupling reactions provide efficient access to structurally diverse derivatives. Current synthesis methods focus on environmentally benign methodologies incorporating microwave irradiation, ultrasonic activation, and organocatalytic processes. Structure-activity relationship studies indicate that electronic and steric properties of aromatic substituents significantly influence biological potency. The mechanistic basis for biological activity involves interactions with cellular targets including tubulin, cyclooxygenases, and various kinases. Green chemistry techniques continue to advance the field by improving reaction efficiency while minimizing environmental impact